Pengaruh Katalis Zeolit terhadap Mass Balance dan Sebaran Senyawa Hidrokarbon pada Minyak Hasil Pirolisis Limbah Plastik - Prabuditya Bhisma Wisnu Wardhana; Nur Hayati; Gunawan Budi Susilo; Beni Tri Sasongko (Jurnal Kendali Teknik dan Sains, 2025)
The problem of plastic waste has developed into an urgent global environmental crisis, due to the nature of plastic that is difficult to decompose and can persist in the environment for hundreds of years. This study explores pyrolysis as a promising oxygen-free thermal conversion technology to overcome plastic waste by converting it into valuable products such as oil, gas, and char. The main focus of the study is the use of zeolite catalysts in the pyrolysis of polyethylene plastic waste from household waste, with a total mass of 1.5 kg of plastic waste and 200 grams of zeolite catalyst. The catalyst used, natural zeolite from Klaten, Central Java, was heated at a temperature of ±200°C before being used in a pyrolysis reactor at an operating temperature of 450°C for ±4 hours. The results showed that the use of zeolite catalysts reduced the percentage of liquid and solid products, but increased the percentage of gas products. In addition, the use of catalysts tended to reduce the content of medium fractions (C11-C22) and paraffin fractions, while increasing the light fractions (C4-C11) and olefin fractions. These findings indicate the potential of pyrolysis as a sustainable solution to the plastic waste problem with positive impacts on the environment and economy.